Realistic mathematics education (RME) to improve literacy and numeracy skills of elementary school students based on teachers’ experience - Fauzan, Ahmad; Harisman, Yulyanti; Yerizon, Yerizon; Suherman, Suherman; Tasman, Fridgo; Nisa, Sahrun; Sumarwati, Sumarwati; Hafizatunnisa, Hafizatunnisa; Syaputra, Hamdani (Jurnal Infinity, 2024)
Literacy and numeracy are the abilities of students to use basic mathematics in solving daily life problems, and students should have it. Various studies have shown that Indonesian students' literacy and numeracy skills still need to improve. One of the solutions to this problem is RME, and one of the components that influence this skill is teachers as a facilitator and their experiences. Thus, this research aims to refigure how students who receive Realistic Mathematics Education (RME) literacy and numeracy skills improve based on teacher's experiences. The research subjects are third, fourth, and fifth-grade students in elementary schools in Padang. Three schools were selected for each grade level and taught by three teachers with different experiences. The students were given literacy and numeracy problems before and after RME instruction. The answers were assessed and grouped to examine the student's literacy and numeracy achievement. The research results show that student's literacy and numeracy skills are better with RME learning. Student's literacy and numeracy skills are not influenced by teachers' experience.